2017
DOI: 10.1016/j.jamda.2017.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of a Proactive Primary Care Program for Frail Older People: A Cluster-Randomized Controlled Trial

Abstract: A proactive screening intervention has a high probability of being cost-effective compared to usual care. The combined intervention showed less value for money.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…The results of this study enhanced our understanding of the treatment fidelity (e.g., how the evidence‐based nurse‐led primary care program was delivered during the trial). The delivery of the care program is probably associated with the obtained trial results that showed a small but significant effect on the preservation of daily functioning (Bleijenberg, Drubbel et al., ). First, the results of this study showed that the nurse‐led intervention program was suboptimally implemented: only one‐third of the older people who reported to have (some) problems at one or more conditions (e.g., cognition or nutrition) did receive further diagnostic assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study enhanced our understanding of the treatment fidelity (e.g., how the evidence‐based nurse‐led primary care program was delivered during the trial). The delivery of the care program is probably associated with the obtained trial results that showed a small but significant effect on the preservation of daily functioning (Bleijenberg, Drubbel et al., ). First, the results of this study showed that the nurse‐led intervention program was suboptimally implemented: only one‐third of the older people who reported to have (some) problems at one or more conditions (e.g., cognition or nutrition) did receive further diagnostic assessment.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of this program combined with a frailty screening instrument has been evaluated in a three‐armed cluster randomized trial with over 3,000 older people in the Netherlands. After 1 year of follow‐up, a relatively small, but significant effect on the primary outcome of daily functioning was observed, with beneficial effects for well‐educated older people (Bleijenberg, Drubbel et al., ). Besides an evaluation of the effectiveness, information regarding the delivery of the intervention is required to fully understand how the results were obtained and to facilitate replication.…”
Section: Introductionmentioning
confidence: 99%
“…Three later randomised trials of CGA in the Netherland’s frailty care programme found almost no clinical benefits 31. Available evidence for cost effectiveness is inconsistent and inconclusive 173132…”
Section: Challenges To Adopting the Frailty Agenda In Primary Carementioning
confidence: 99%
“…Colonoscopy every 10 years No Screening 60-year-old Swedish Lifetime Healthcare 3% EUR (no year) QALYs No All strategies were CE vs no screening SCREESCO study Yes Atkin et al [ 18 ] UK Colorectal cancer 13 different Sttrategies Each other and “no colonoscopy” Individuals with intermediate-grade adenomatous polyps Lifetime NHS 4% 2012–2013 GBP QALYs, ELYs Yes 3-yearly ongoing colonoscopic surveillance without an age cut-off is CE NIHR Yes Baggaley et al [ 75 ] UK HIV INSTI HIV1/HIV2 rapid antibody test Not clear Hackney Borough 40 years NHS 4% 2012 GBP QALYs Yes Screening is CE NHS, NIHR Yes Barzi et al [ 19 ] USA Colorectal cancer 13 screening tools: fecal occult blood test, Flex sig, colonoscopy, CT, DNA. No screening US population 35 years Societal 3% USD (no year) Life years gained No Colonoscopy is CE National Cancer Institute Core Yes Bleijenberg et al [ 13 ] Netherlands Frailty 1. Electronic frailty screening instrument (EFSI) 2.…”
Section: Resultsmentioning
confidence: 99%